A return to performance framework to effectively complete the rehabilitation continuum for elite soccer - Choice, E.; Hooker, K.; Downey, R.; Haugh, G. (Strength and Conditioning Journal, 2024)
Return from sport-related injury requires interprofessional collaboration to progress the athlete through a multistage rehabilitation continuum and successfully re-establish a performance level at or above the preinjury level. To achieve an optimal rehabilitation outcome, evidence-based exercise prescription must be considered throughout the entire continuum alongside typical milestones and testing outcomes. This prescription must also use match-play external load data within a multisystems program. This applied article focuses on the physical characteristics and training aspects after anterior cruciate ligament reconstruction and throughout the full rehabilitation continuum which includes 3 general phases: return to activity, sport, and performance. A 5 step framework is provided for the strength and conditioning specialist to effectively transition elite soccer athletes from return to sport to return to performance. This framework includes an expanded definition of the role of the strength and conditioning specialist during rehabilitation and outlines exercise prescription across the entire rehabilitation continuum. Improved interprofessional collaboration, decision making, and load management throughout transitions can aid in optimizing long-term outcomes for the athlete, including reduced risk of reinjury or new injury.